The Efforts to Implement Diversion to Realize Restorative Justice for Children in Conflict with the Law in the Juvenile Criminal Justice System - Hendra Wahyudi; Umar Ma'ruf; R. Sugiharto Sugiharto (Universitas Islam Sultan Agung, 2022)
One form of legal protection for children is to realize the fulfillment of the rights and obligations of the child itself. Especially for children in conflict with the law, their problem solving process requires special attention. This study aims to analyze the application of diversion in restorative justice for children who are in conflict with the law in the juvenile criminal justice system. The type of research conducted is descriptive research with the type of normative legal research related to the application of diversion in restorative justice in the criminal justice system. The results showed that the application of diversion in restorative justice in the system of applying diversion to children in conflict with the law in the juvenile justice system, is the implementation of a system in restorative justice to provide justice and legal protection to children in conflict with the law without ignoring the child's criminal responsibility. Diversion is not a peaceful effort between children in conflict with the law and the victim or his family, but a form of punishment for children in conflict with the law in an informal way. The recommendation in this study is that law enforcement officers in carrying out their duties of investigating, prosecuting, examining and determining case decisions at court trials should prioritize the application of diversion as an alternative to the application of imprisonment. Massive socialization of diversion is needed to the community.